Model Manajemen Pendidikan Keluarga Muslim dalam Quran - Pradipa, Rafi; Subiyantoro, Subiyantoro; Dewi, Siska; Karwadi, Karwadi; Nasruddin, Muhammad (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
This article formulates a model of child education management in Muslim families based on Islamic values using the POAC (Planning, Organizing, Actuating, Controlling) framework. Employing a library research method, the study reviews the Qur’an, Hadith, and Islamic literature. The findings indicate that child education management can be structured into four main stages: planning, which emphasizes instilling tauhid from an early age (QS. Luqman: 13); organizing, through role distribution and family responsibilities in accordance with the principle of qawwam (QS. An-Nisa: 34); actuating, realized through role modeling, advice, worship practices, and moral education (QS. Luqman: 14–17); and controlling, which emphasizes fair reward and punishment (QS. Az-Zalzalah: 7–8). This model integrates modern management theory with Islamic teachings and provides a practical guide for Muslim families to nurture children who are faithful, virtuous, and responsible.